Field trips based on a focused strategy to stimulate the improvement of students' problem-solving skills on ecosystem materials - Saefudin Saefudin; Ari Permana; Amprasto Amprasto (JURNAL BIOEDUKATIKA, 2022)
Improving problem-solving skills has been promoted as a helpful strategy in student learning in the 21st century. Field trips are a learning method that can encourage students to interact directly with natural objects in nature. The learning method is expected to improve students' problem-solving skills. In this case, this research was conducted to find the effect of field trips on improving students' problem-solving skills based on a focused strategy. This research is quasi-experimental research using pre-test and post-test designs. The participants in this study were students from two tenth grades of SMAN in Pameungpeuk, Garut, during the 2019/2020 school year. The data obtained were analyzed using the average comparison test, namely the t-test (for parametric data) and the Mann-Whitney test (for non-parametric data) with a value of 0.05. Based on the analysis, the problem-solving skills of students in the two classes increased in the medium category, and there was a significant difference in the problem-solving skills of students in the two classes with a significant value of 0.044. Thus, it can be concluded that a focused strategy-based field trip affects problem-solving skills and can stimulate the improvement of students' problem-solving skills on ecosystem materials. Therefore, a field trip with a focused strategy can potentially be an alternative method for teachers in high school to improve students' problem-solving skills on ecosystem materials.